Growth behavior and electronic properties of Gen + 1 and AsGen (n = 1–20) clusters: a DFT study. (March 2019) - Benaida, M.; Aiadi, K. E.; Mahtout, S.; Djaadi, S.; Rammal, W.; Harb, M.
Abstract: We present a systematic computational study based on the density functional theory (DFT) aiming to high light the possible effects of one As doping atom on the structural, energetic, and electronic properties of different isomers of Ge n + 1 clusters with n = 1–20 atoms. By considering a large number of structures for each cluster size, the lowest-energy isomers are determined. The lowest-energy isomers reveal three-dimensional structures starting from n = 5. Their relative stability versus atomic size is examined based on the calculated binding energy, fragmentation energy, and second-order difference of energy. Doping Ge n + 1 clusters with one As atom does not improve their stability. The electronic properties as a function of the atomic size are also discussed from the calculated HOMO–LUMO energy gap, vertical ionization potential, vertical electron affinity, and chemical hardness. The obtained results are significantly affected by the inclusion of one As atom into a Ge n cluster.